The mixed economy of long-term care in England, Germany, Italy, and Spain - Heinz Rothgang; Adelina Comas-Herrera; Raphael Wittenberg; Linda Pickard; Cristiano Gori; Alessandra Pozzi Di Maio; Joan Costa-Font; Concepció Patxot (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2004)
This paper is based on a European Commission-funded study of future long-term care expenditure in Germany, Italy, Spain and the United Kingdom. It investigates how sensitive long-term care expenditure is to assumptions about demographic trends, future dependency rates, care arrangements, and real inflation. Macro-simulation projection models for each country reflecting the national characteristics of the care system were used to make comparable projections based on a set of common assumptions. This central case was then used as a point of comparison in order to explore the sensitivity of the models to alternative scenarios about key determinants of future expenditure. The proportion of GDP spent on longterm care is projected to more than double between 2000 and 2050 in each country under the central case. However, projections are highly sensitive to changes in the above assumptions. – – Der Beitrag beruht auf einer EU-finanzierten Studie zur zukünftigen Entwicklung der Ausgaben für Langzeitpflege in Deutschland, Italien, Spanien und dem Vereinigten Königreich. Untersucht wird die Sensitivität der Ausgabenentwicklung hinsichtlich unterschiedlicher Annahmen zur demographischen Entwicklung, zur Pflegebedürftigkeit, zur Pflegeform und zu den Kosten der Pflege. Mittels nationaler Makrosimulationsmodelle, die die länderspezifischen Pflegesysteme berücksichtigen, wird ein auf gemeinsamen Annahmen basierendes Grundmodell berechnet, das den Referenzpunkt der nachfolgenden Sensitivitätsanalyse darstellt. Im Ergebnis zeigt sich in allen Untersuchungsländern, dass sich der Anteil des BIP, der für Pflegeleistungen aufgewandt wird, von 2000 bis 2050 mehr als verdoppelt. Allerdings sind diese Ergebnisse sehr sensitiv in bezug auf Veränderungen der genannten Annahmen.
Keywords: 300